Length-Weight Relationship and Negative Allometric Pattern of Male Mackerel (Rastrelliger kanagurta) at Sorong Fish Landing Site, Southwest Papua - Max Siaila; Roger R. Tabalessy; Melisa Masengi (INTEGRATED OF FISHERIES SCIENCE, 2025)
Rastrelliger kanagurta is a small pelagic fish commodity with high economic value and is vulnerable to overfishing. This study aimed to analyze the length-weight relationship as an indicator of growth pattern of Indian mackerel landed at the Fish Landing Site (TPI) of Sorong City, West Papua. Sampling was conducted purposively from April to June. A total of 191 fish were measured for total length (mm) and body weight (g). The length-weight relationship was analyzed using logarithmic linear regression, followed by a t-test to determine the growth pattern (isometric or allometric). The results showed that the caught fish were dominated by the length class of 185.5–200.5 mm (31.9%) and weight class of 71.5–86.5 g (28.3%). The combined regression coefficient b (April–June) was 2.2498, with a calculated t-value (1.6125) < t-table (1.9725) at 95% confidence level, indicating a negative allometric growth pattern. This means that length gain is faster than weight gain, suggesting relatively slender body condition, presumably due to fishing pressure or food limitation. These findings confirm that the population of Indian mackerel in Sorong waters has experienced a shift in growth pattern, necessitating adaptive management measures such as mesh size regulation and enhanced monitoring of fishing grounds